A Study On Prescription Pattern and Cost Analysis of Antiretroviral Drugs - SANKAR VEINTRAMUTHU,; RUCKMANI KANDASAMY,; VELAYUTHAM KANNIYAPPAN,; NITHYANANTH MUNUSAMY, (International Journal of Pharma and Bio Sciences, 2010)
In HIV infectious disease, anti-retroviral drugs have to be taken for a long duration. Prescribing costly antiretroviral drugs to patient increases the expenditure during treatment. This can be solved by prescribing the drugs with low cost or generic products. In India 136 different brands of Anti-retroviral drugs are available. Out of this 40 brands are available in combination. In the present study we have analyzed the difference in the cost of Anti-retroviral combinational drugs of different brands which will help the physician to prescribe cheaper brands. The cost ratio of combination of drugs varies from 1.10 to 3.867.